Efficient ternary blend all-polymer solar cells with a polythiophene derivative as a hole-cascade material. Issue 38 (14th September 2016) - Su, Wenyan; Fan, Qunping; Guo, Xia; Guo, Bing; Li, Wanbin; Zhang, Youdi; Zhang, Maojie; Li, Yongfang
Abstract : Efficient ternary all polymer solar cells (all-PSCs) based onPTB7-Th :PBDD-ff4T :N2200 were reported, wherePTB7-Th andPBDD-ff4T were two polymer donors andN2200 was a polymer acceptor. The all-PSCs showed an optimized PCE of up to 7.2% which is superior to those of the binary all-PSCs based onPTB7-Th :N2200 andPBDD-ff4T :N2200 . Abstract : Ternary blending is one of the effective strategies to broaden the complementary absorption range and smooth the energy level at the donor/acceptor interface for achieving high efficiency bulk heterojunction (BHJ) polymer solar cells (PSCs). In this study, we report efficient ternary blend all-polymer solar cells (all-PSCs) with complementary absorption bands based on two polymer donorsPTB7-Th andPBDD-ff4T and one polymer acceptorN2200 . The polythiophene derivativePBDD-ff4T as a hole-cascade material plays a bridging role in energy levels betweenPTB7-Th andN2200, and thus provides more efficient channels for charge transfer. The ternary all-PSCs with 10 wt%PBDD-ff4T content show efficient photon harvesting, enhanced charge mobility and better active layer morphology due to the induced crystallization ofPTB7-Th by the insertedPBDD-ff4T in the donor domains. As a result, the device without any extra treatments exhibits an optimized power conversion efficiency (PCE) of 7.2% with an open circuit voltage ( V oc ) of 0.82 V, a short circuit current density ( J sc ) of 15.7 mA cm −2, and a fill factor (FF) of 56%. While the PCEs are 5.9% and 4.2% for the all-PSCs based on the binary blendsPTB7-Th :N2200 andPBDD-ff4T :N2200, respectively. This PCE of 7.2% is one of the highest values reported in the literature so far for ternary all-PSCs and polythiophene derivative-based all-PSCs.